Drug Dosing in Pediatrics: Possible Approaches - Alexey S. Kolbin; Kseniya S. Radaeva ("Paediatrician" Publishers LLC, 2023)
Drug dosing remains one of the topical issues of modern pediatrics. Insufficient number of clinical studies, vulnerable patient populations (preterm newborns, patients with renal and/or hepatic insufficiency, obesity), and high risk of polypragmasy create additional difficulties for practicing physicians. This review provides description of currently used approaches to drugs dosing in children. It has been shown that prognostic models should be used for solving drugs dosing issues regarding characteristics of young patients. Such models include: physiologically based pharmacokinetic modelling; population pharmacokinetic analysis; model-based precision dosing; modeling and simulation approach; use of real world data; and pharmacogenetic testing-based dosing. These models use information from preclinical and clinical stu